Entrepreneurial Education In Times Of Turmoil: A Qualitative Analysis Of Adaptation Strategies During The COVID-19 Pandemic - Endang Prihatin; Defifi Ismiyati (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study explores adaptation strategies employed in entrepreneurial education during the COVID-19 pandemic. The research aims to understand the response mechanisms adopted by educational institutions and stakeholders to address challenges posed by the crisis. Employing a qualitative research design, semi-structured interviews and document analysis are utilized to gather data from educators, administrators, and entrepreneurs. Thematic analysis is employed to uncover patterns, emerging themes, and insights from the data. Results reveal innovative approaches such as virtual learning platforms, mentorship programs, and agile curriculum adjustments. Additionally, challenges such as digital divide and resource constraints are identified. This study contributes to the discourse on educational resilience during crises and offers insights for policymakers and educators in fostering adaptive learning environments.